The Teacher's Introduction to Pathological Demand Avoidance : Essential Strategies for the Classroom. - Truman, Clare (London : Jessica Kingsley Publishers, 2021)
"This essential guide for working with PDA pupils outlines effective and practical ways that teachers and school staff can support these pupils, by endorsing a child-led approach to learning and assessment. Beginning with an introduction to PDA and how it can affect the education experience, the book is then followed by thoughtful, useful strategies school staff can implement to build a collaborative relationship with pupils and help them to thrive in the school environment. The activities presented aim to make children more comfortable and at ease, and therefore better able to learn. It covers key issues for children with PDA, such as sensory issues, preferred language and phrasing of demands, social skills, and recognising distressed behaviour. The chapter summaries and simple activities listed throughout make this a useful tool for busy teaching staff working with PDA pupils"--
Intro -- The Teacher's Introduction to Pathological Demand Avoidance -- Cover -- Of related interest -- Title page -- Copyright -- Contents -- Acknowledgements -- Preface -- 1. PDA -- What Do We Know So Far? -- 2. Prioritizing Demands -- 3. Presenting Demands -- 4. Designing and Implementing a Child-Led Curriculum -- 5. Invitations to Learn -- 6. Developing Social Understanding -- 7. Adapting Traditional Autism Strategies -- 8. Managing Distressed Behaviour -- 9. Hidden Forms of Distressed Behaviour -- 10. Managing the Needs of the PDA Student in a Class of Thirty -- 11. Eating, Drinking, Washing -- 12. Paperwork -- 13. What I Learnt from Spectrum Space -- Afterword -- Further Advice and Further Reading -- References -- Index.
Description based upon print version of record.
eBooks on EBSCOhost
Keywords: Learning disabled children -- Education; Pathological demand avoidance syndrome; Classroom environment; Enfants en difficulté d'apprentissage -- Éducation.; Salles de classe -- Environnement; Behavioral; Special Education; EDUCATION; Child; Developmental; PSYCHOLOGY; Autism Spectrum Disorders; Psychopathology; SELF-HELP.; Classroom environment; Learning disabled children -- Education; Pathological demand avoidance syndrome